Connecting a missing link between participation in administration and political participation: the mediating role of political efficacy. (December 2017) - Oh, Youngmin; Lim, Seunghoo
Public participation in administrative or political processes has been advocated as an important democratic reform by scholars and practitioners. Despite the importance of such public participation mechanisms, the relationship between participation in administration and political participation remains unexplored. This study aims to connect the missing link by empirically testing the mediating roles of political efficacy between two types of public participation. By connecting administrative and political participation through political efficacy, we intend to demonstrate that citizen participation in administration plays a pivotal role in remedying declining political participation. For the empirical tests, cross-sectional data from local jurisdictions in Korea were collected by survey questionnaires, and a series of Structural Equation Models are used to identify the causal relationships among these variables. The findings demonstrate that participation in administration influences political participation only through political efficacy, while the demand for participation in administration is connected to political participation either directly or through internal political efficacy. Conversely, political participation fosters participation in administration only through political efficacy. Given the empirical evidence, participation in administration and political participation reinforce each other, and political efficacy plays a critical role in mediating the two types of public participation. Points for practitioners: Borrowing the concept of political efficacy, this study sheds theoretical light on a missing link between administrative and political participation. Practitioners need to realize that devising authentic administrative programs is a useful way to remedy waning democratic participation. Practitioners need to suggest many specific ideas on how to foster citizens' political efficacy through public participation. By doing this, citizens could be politically awakened, which would lead to their increased participation. In this sense, this study is an initial step in exploring the possibility of democratic benefits produced by public participation mechanisms beyond the normative and instrumental benefits.